Auditory and Vestibular Functioning in Individuals with Type-2 Diabetes Mellitus: A Systematic Review - Kumar,Prawin (2022)
Abstract Introduction Diabetes mellitus is a metabolic disease associated with a rise in the level of blood glucose. Individuals with diabetes mellitus are more likely to develop hearing loss, tinnitus, and dizziness due to macro- and microvascular complications. The extent to which auditory and vestibular functions are impaired in individuals with type-2 diabetes mellitus is still under debate. Objective To systematically review studies focusing on auditory and vestibular functions in individuals with type-2 diabetes mellitus. Data Synthesis A search was conducted in the PubMed, MedlinePlus, Ingenta Connect and Google Scholar databases for articles published until June 2019. A total of 15,980 articles were primarily retrieved, 33 of which were shortlisted based on the inclusion criteria set by the investigators for the systematic review. Out of 33 full-length articles, 26 evaluated the functioning of the auditory system, while 7 evaluated the functioning of the vestibular system. Most studies related to auditory functioning reported a significant effect of type-2 diabetes mellitus on the peripheral auditory system, whereas studies on vestibular functioning reported no significant effect of diabetes mellitus on the functioning of the peripheral vestibular end-organ. Conclusion Overall, the results of various audiological and peripheral vestibular tests reveal distinctive peripheral and/or central auditory and vestibular end-organ impairments in individuals with type-2 diabetes mellitus.